Could horse grazing be used to restore abandoned fields? : a comparison of the vegetation between horse pastures and abandoned fields, and an inventory of the effects of grazing- history and intensity - Vogel, Jantien (SLU/Dept. of Wildlife, Fish and Environmental Studies, 2022)
Semi-natural fields, created by traditional land-use systems like low-intensity cattle grazing, have high ecological value due to the occurrence of numerous plant species, and their associated faunal communities. In Sweden, this habitat is threatened by both land-abandonment and agricultural intensification. Reintroduction of low intensity grazing by large herbivores at abandoned sites might enable restoration of this habitat. The aim of this study is to investigate the potential of horses to benefit a grazing associated, diverse plant community. I surveyed forbs within 20 horse pastures and 20 abandoned fields, to evaluate how horse grazing affects the vegetation. Within the horse pastures, the effect of grazing- history and intensity was analysed. The forb community composition differed clearly between horse pastures and abandoned fields. Forb species richness tended to be higher in horse pastures, which were dominated by ruderal, grazing associated species, whereas forb communities on abandoned fields mainly consisted of competitive forb species. Eight semi-natural pasture species were found, primarily within horse pastures. Forb species at horse pastures had a lower canopy hight and lower seed mass, which are two known grazing associated traits. Contrary to expectations, specific leaf area (SLA) was higher at abandoned fields, despite the fact that high SLA is associated with grazing tolerance. Horse pastures had a higher number of plants that are pollinated by pollinators from different taxa (generalists), the number of bee-pollinated and wind-pollinated species did not differ. Grazing history affected species richness, which was lower in newly grazed pastures (< 6 years) compared to pastures that had been grazed for over 15 years. Furthermore, more generalist-pollinated species were present in these older (>15) pastures, compared to the pastures that were grazed for less than 6 years. There were no effects of grazing intensity. This study shows that horses are able to create more diverse, grazing associated plant communities compared to abandoned sites, and that species richness increases after the first 5 years of grazing. However, it has to be noted that both habitats sustain very different plant communities, on which different species might be reliant. Furthermore, few semi-natural pasture species were found within horse pastures, which might be due to lack of source populations. Nevertheless, horse grazing could have the potential to restore abandoned fields. More research is needed on how to benefit targeted species, e.g. by varying the time slot of grazing and mowing, and by investigating the availability of source populations.